Progress to Control and Eradication of Peste des Petits Ruminants in the Southern African Development Community Region - Britton, Andrea; Caron, Alexandre; Bedane, Berhanu (Frontiers in Veterinary Science, 2019)
In southern Africa, small ruminants are an important source of nutrition and income to resource-poor small-holder farmers. After spreading from West to Central and Eastern Africa, Peste des Petits Ruminants (PPR) emerged in the United Republic of Tanzania in 2008 and has since been reported in Angola, the Democratic Republic of the Congo, and the Comoros. The disease can cause considerable morbidity and mortality in naïve sheep and goat populations and severely impact rural livelihoods especially women. Gaps of knowledge still exist in PPR epidemiology, notably regarding the extent of small-ruminant animal movements and the role of the abundant wildlife in southern Africa. The capacity of veterinary services to undertake surveillance and control PPR is heterogeneous within the region, with vaccination being limited. The Pan African strategy for the control and eradication of PPR mirrors the Global Strategy and provides the framework for the Southern African Development Community region to meet the 2030 goal of eradication. Five countries and one zone within Namibia are officially PPR free according to OIE Standards. Most countries have developed National Strategies for the control and eradication of PPR. To strengthen the national and regional PPR eradication programme, there is a need for a regional risk-based surveillance adapted to infected, high-risk and lower-risk countries that will enable targeted and efficient control, rapid response to incursions and prevention of spread as well as improved preparedness. Continued international support will be necessary including laboratory diagnostics and enhancing surveillance capacity to prevent further spread southwards on the continent.